1997
DOI: 10.1136/hrt.78.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial appendage function in patients with atrial flutter.

Abstract: Objective-To determine whether echocardiographic markers of thromboembolic risk differ between patients with pure atrial flutter and patients with atrial flutter and intermittent atrial fibrillation. Design-Patients with atrial flutter were followed up prospectively for 12 months to identify intermittent atrial fibrillation. After the follow up period, transthoracic and multiplane transoesophageal echocardiography were performed to assess left atrial chamber and appendage size, peak emptying velocities, and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…In atrial utter, the LAA function seems to be preserved as expressed by higher LAA velocities and lower rates of SEC. 21 Our study found no correlation between the frequency of LAA contractions and its emptying velocity. Only three of our patients had frequency of LAA contractions # 5 Hz.…”
Section: Characterization Of Laa Function In Patients With Afcontrasting
confidence: 73%
“…In atrial utter, the LAA function seems to be preserved as expressed by higher LAA velocities and lower rates of SEC. 21 Our study found no correlation between the frequency of LAA contractions and its emptying velocity. Only three of our patients had frequency of LAA contractions # 5 Hz.…”
Section: Characterization Of Laa Function In Patients With Afcontrasting
confidence: 73%
“…Utilizing TEE, further depression of left atrial appendage ejection velocities, more intense left atrial spontaneous echocardiographic contrast, and even new thrombus formation have been described after external DC, internal DC, and spontaneous cardioversion. [235][236][237][238] These data underscore the importance of therapeutic anticoagulation during the peri-cardioversion period. Following restoration of normal atrial electrical activity on the surface ECG, the mechanical contraction of the body of the left atrium may remain dysfunctional for as long as 2 to 4 weeks after cardioversion.…”
Section: Anticoagulation For Elective Cardioversion Of Afmentioning
confidence: 82%
“…Atrial flutter is known to result in a higher LAA flow velocity than AF or fibrillation-flutter. 19,20 Although in contrast to the findings of Li et al, 4 one would then expect a better LAA function in patients with coarse AF. 21 This was noted partially in patients in the current study.…”
Section: Determinants Of Fibrillatory Wave Formmentioning
confidence: 79%